Environmental Sampling and Analysis for Metals - Csuros, Maria (CRC Press, 2009)
Determination of metals is a major part of the work of environmental testing laboratories. EPA and DEP methodology releases provide information only for selected areas of metals sampling and analysis, and their language makes them unsuitable for teaching and training purposes. Environmental Sampling and Analysis for Metals is a comprehensive and easy-to-read text for laboratory technicians and analytical chemists who need a guide for analyzing metals in environmental samples and a reference for analytical and quality control procedures.